Etat Des Lieux Et Evaluation Des Formations En Radiologie Dans Un Pays En Developpement, Cas Du Togo - Tchaou, Mazamaesso; Houadjeto, Dandjeffo L. C.; Sonhaye, Lantam; Agoda-Koussema, Lama-Kegdigoma; Adjenou, Komlanvi; N’dakena, Koffi (European Scientific Journal, ESJ, 2018)
Objective: to make an inventory and assess the training in radiology in Togo. Methodology: Descriptive study, with opinion survey, carried out from June to August 2016 including students in Master and Residents in radiology of the academic year 2015 - 2016. Results: The response rate was 91%. All the training sites had conventional radiography and functional ultrasound. For 57% of students the quality of practical instruction was 4/5. The availability of teachers was acceptable (3/5) to good (4/5) according to 84%. Competence for examinations varies from bad (2/5) to excellent (5/5) for the Master 1 and from good to excellent in Master 2. The difference in responses was not significant regardless of the year of study or training course (p> 0.05). For the performance and interpretation of radiological examinations, the junior residents were considered mediocre (1/5) to acceptable versus acceptable to seniors. For an ultrasound, this score varied from 1/5 for the juniors residents to 4/5 for the seniors. The competence to carry out a vessels ultrasound Doppler was 1/5 for the junior residents and 2/5 for the senior. Conclusion: Learners in radiology in Togo are generally satisfied with the training they receive. Acquisitions of significant skills have been observed from one level of training to another.